AI IN CYBER DEFENSE: PRIVACY RISKS, PUBLIC TRUST, AND POLICY CHALLENGES - Azizi, Abdullah; Mohammadi, Mohammad Qias; Samadzai, Abdul Wahid (Jurnal Ilmiah Dinamika Sosial, 2025)
The rapid integration of Artificial Intelligence (AI) into cybersecurity systems, particularly AI-based cyber defense systems, is reshaping the landscape of digital security. This study explores the social impacts of these systems, focusing on privacy, security, and public trust. The purpose of this research is to examine the effects of AI-driven cybersecurity on individuals and society, addressing concerns such as privacy risks, security breaches, and trust in digital platforms. A systematic literature review (SLR) methodology was employed, synthesizing relevant academic studies, conference proceedings, and reports from credible databases, including IEEE Xplore, ACM Digital Library, and ScienceDirect. The results reveal that while AI-based systems improve threat detection and response times, they also raise significant concerns about data privacy, surveillance, and the potential for algorithmic bias. Additionally, the integration of AI in cyber defense has prompted debates on the ethical implications of automated decision-making and the transparency of these systems. In conclusion, while AI offers transformative benefits in cybersecurity, careful attention is required to balance its advantages with ethical and privacy considerations. This study emphasizes the need for ethical frameworks and public awareness to ensure that AI-based systems are deployed in a manner that fosters trust and protects citizens' rights.